2018
DOI: 10.1093/ntr/nty235
|View full text |Cite
|
Sign up to set email alerts
|

Free-Base and Total Nicotine, Reactive Oxygen Species, and Carbonyl Emissions From IQOS, a Heated Tobacco Product

Abstract: Introduction IQOS is an emerging heated tobacco product marketed by Philip Morris International (PMI). Because the tobacco in IQOS is electrically heated and not combusted, PMI claims that it generates significantly lower toxicant levels than combustible cigarettes. To date, a few independent studies have addressed IQOS toxicant emissions, and none have reported reactive oxygen species (ROS), and the form of the nicotine emitted by the device. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 19 publications
4
61
1
Order By: Relevance
“…The results of independent studies have shown that IQOS emit substantially lower levels of carbonyls and submicronic particles than a commercial cigarette but higher levels than an e-cigarette [25,26,28]. The emission of reactive oxygen species during IQOS use points to potentially harmful effects of IQOS use, such as cancer or pulmonary diseases [38]. Moreover, an independent review of preclinical and clinical data on IQOS has revealed the possible hepa-IJOMEH 2019;32 (5) companies use dedicated hashtags and advertising slogans to promote HTPs on their websites [96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of independent studies have shown that IQOS emit substantially lower levels of carbonyls and submicronic particles than a commercial cigarette but higher levels than an e-cigarette [25,26,28]. The emission of reactive oxygen species during IQOS use points to potentially harmful effects of IQOS use, such as cancer or pulmonary diseases [38]. Moreover, an independent review of preclinical and clinical data on IQOS has revealed the possible hepa-IJOMEH 2019;32 (5) companies use dedicated hashtags and advertising slogans to promote HTPs on their websites [96].…”
Section: Discussionmentioning
confidence: 99%
“…Leigh et al also observed that IQOS emitted lower amounts of tobacco-specific nitrosamines than combustible cigarettes, but a significantly higher amount than e-cigarettes [37]. Salman et al reported that the use of IQOS emitted significant levels of reactive oxygen species and carbonyl compounds, but these were still 85% and 77% lower than the levels emitted by combustible cigarettes [38]. Jaccard [13] Japan Tobacco to analyze the impact of using a novel tobacco vapor product (the Ploom TECH prototype) on indoor air quality the Ploom TECH prototype; an environmentally controlled chamber; 3 environments: 2 non-smoking areas and 1 smoking area; indoor air quality was evaluated by: 1) measuring the constituents in mainstream emissions, 2) by determining the classic environmental tobacco smoke and 3) by representative air quality markers -the mainstream emissions of vapor from Ploom TECH were chemically simpler than those of cigarette smoke environmental tobacco smoke markers, volatile organic compound (toluene), carbon monoxide, propylene glycol, glycerol, and triacetin were below the limit of detection, or the limit of quantification, in both the non-smoking and smoking environments after using the Ploom TECH no significant increase in the levels of formaldehyde, acetone or ammonia in the exhaled air were observed following Ploom TECH use -Ploom TECH had no measurable effect on the indoor air quality CO -carbon monoxide; HCI -Health Canada Intense; HTPs -heated tobacco products; ISO -International Organization for Standardization; SMPs -submicronic particles; THS2.2 -tobacco heating system 2.2 (IQOS); TSNA -tobacco-specific nitrosamines; PMI -Philip Morris International; VOCs -volatile organic compounds; 3R4F -reference cigarette.…”
Section: Chemical Composition Of Tobacco Sticksmentioning
confidence: 99%
“…In accordance with the principle of temperature dependence of HPHC generation in tobacco products, the question of reduced HPHC levels in the emissions was raised. While manufacturers provided the initial studies (1518), more and more independent investigations have now been published for commercially available products (1929). These studies were focused on levels of well-known HPHCs in comparison with other tobacco products.…”
Section: Emissionsmentioning
confidence: 99%
“…Typically, PODs were lower for 1R6F bPBS when compared to 3R4F bPBS, which is also reflective of the increase in quantified constituents captured in PBS for 1R6F over 3R4F. These changes also reflected differences in ROS measured in both IQOS and cigarettes ( Salman et al, 2019 ) with the increased ROS measured linked with the decreased cystine seen for these products ( Dypbukt et al, 1994 ). These results support the risk continuum positioning of non-combustible nicotine products relative to combustible cigarettes.…”
Section: Discussionmentioning
confidence: 97%